Pengaruh Digitalisasi Pajak dan Kesadaran Wajib Terhadap Kepatuhan Wajb Pajak di RPK Perum Bulog Lembang - Marbun, Alvario; Sudjiman, Lorina Siregar; Waty, Lenita (Peneliti.net, 2026)
This study aims to analyze the influence of tax digitalization and taxpayer awareness on taxpayer compliance among MSMEs in the RPK Perum BULOG Lembang. This study used a quantitative approach with an explanatory survey design. Data were collected through questionnaires from 86 respondents using a purposive sampling technique. Data analysis used multiple linear regression. The results indicate that tax digitalization and taxpayer awareness have a positive and significant effect on taxpayer compliance, both partially and simultaneously. The coefficient of determination (R2) of 0.852 indicates that 85.2% of the variation in taxpayer compliance can be explained by these two variables. This finding underscores the importance of digital tax system integration and increased taxpayer awareness in encouraging compliance, particularly in the MSME sector.